Herceptin-conjugated paclitaxel loaded PCL-PEG worm-like nanocrystal micelles for the combinatorial treatment of HER2-positive breast cancer. (November 2019) - Peng, Jiahui; Chen, Juan; Xie, Fang; Bao, Wei; Xu, Hongyan; Wang, Hongxia; Xu, Yuhong; Du, Zixiu
Abstract: We have constructed Herceptin-conjugated, paclitaxel (PTX) loaded, PCL-PEG worm-like nanocrystal micelles (PTX@PCL-PEG-Herceptin) for the combinatorial therapy of HER2-positive breast cancer that exploit the specific targeting of Herceptin to HER2-positive breast cancer cells. Firstly, amphiphilic PCL2000 -MPEG2000 and PCL5000 -PEG2000 -CHO were selected as the optimized matrix to wrap PTX that self-assembled into worm-like micelles with internal nanocrystal structures (PTX@PCL-PEG). Then the aldehydes of PCL5000 -PEG2000 -CHO exposed on the outside surface of PTX@PCL-PEG were utilized to react with the primary amines of Herceptin and formed stable, carbon-nitrogen single linkers (–C–N–) between the antibodies and nanoparticles. This study shows PTX@PCL-PEG-Herceptin remained relatively stable in the circulation and in the tumor microenvironment, and rapidly targeted and entered into the HER2-overexpressing tumor cells while sparing normal tissues from the toxic effects. PTX@PCL-PEG-Herceptin shrank the tumors and prolonged survival time in a SKBR-3-tumor-xenograft, nude mice model more effectively than TAXOL®, PTX@PCL-PEG, Herceptin+TAXOL® and Herceptin+PTX@PCL-PEG. Mechanistic studies showed that PTX@PCL-PEG-Herceptin entered into the HER2-positive tumor cells through the caveolin-mediated pathway. The conjugated Herceptin greatly enhanced the binding ability of the nanoparticle to the targeted SKBR-3 cells. This novel strategy provides a rational and simple antibody-conjugated-nanoparticle platform for the clinical application of combinatorial anticancer treatment. Graphical abstract: Image 1